SQL/DS: New Horizons - Eaton, Roger G. (My University, 2016)
One of the virtues of SQL/ OS is an optimizer to perform data access path selection. Because SQL/DS's optimizer determines data access paths, SQL/DS provides the EXPLAIN command to retrieve information about optimizer decisions. You may consider it a window to the instruction will examine (cardinality) and an estimate of the number of times each instruction will executed.
Citation: Eaton, R. (1991). SQL/DS: New Horizons. DATA BASE Management: Data Base Information for the New Era, 1(7), 42-43
Keywords: SQL/DS; Relational Databases; Database Structure